2015
DOI: 10.1371/journal.pone.0134238
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Shared Mechanism in the Formation of Urea-Induced Kinetic and Equilibrium Intermediates of Horse Apomyoglobin from Ultrarapid Mixing Experiments

Abstract: In this study, the equivalence of the kinetic mechanisms of the formation of urea-induced kinetic folding intermediates and non-native equilibrium states was investigated in apomyoglobin. Despite having similar structural properties, equilibrium and kinetic intermediates accumulate under different conditions and via different mechanisms, and it remains unknown whether their formation involves shared or distinct kinetic mechanisms. To investigate the potential mechanisms of formation, the refolding and unfoldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Furthermore, the continuous-flow mixer was employed for the studies on the early stage of folding of whale and horse apoMbs. 37 , 38 , 58 ) More than two intermediates were identified for apoMb folding based on the refolding/unfolding studies of urea-jump at acidic and neutral pHs, monitored by the fluorescence and CD. Laser-induced oxidative labeling after the initiation of folding by rapid mixing was combined with the mass spectrometry-based peptide mapping for the studies on the folding of horse apoMb.…”
Section: Analysis Of the Structure For The Kinetic Intermediate And Imentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the continuous-flow mixer was employed for the studies on the early stage of folding of whale and horse apoMbs. 37 , 38 , 58 ) More than two intermediates were identified for apoMb folding based on the refolding/unfolding studies of urea-jump at acidic and neutral pHs, monitored by the fluorescence and CD. Laser-induced oxidative labeling after the initiation of folding by rapid mixing was combined with the mass spectrometry-based peptide mapping for the studies on the folding of horse apoMb.…”
Section: Analysis Of the Structure For The Kinetic Intermediate And Imentioning
confidence: 99%
“…It was also recently shown that the former-phase kinetic intermediate for apoMb (I1) contains one more intermediate. 37 , 38 ) However, for the purpose of simplifying considerations of this folding system, the I1 intermediate is treated as representing a single structural species in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that for many proteins, equilibrium unfolding intermediates are identical to kinetic unfolding intermediates in terms of their secondary and tertiary structure content, hydrogen exchange protection, collision cross-section, and stability toward unfolding. Hence, mild denaturation conditions can be associated with earlier stages of unfolding. This means that our observation that proteins become more accessible to water at low urea concentrations, indicates that unfolding starts with the protein becoming less tight, allowing water to enter.…”
mentioning
confidence: 99%
“…On the basis of the above considerations and previous studies on pH-induced folding of h- and sw-apoMb, ,, we assumed a five-state sequential model (Scheme ), which is also fully consistent with urea-induced refolding/unfolding at pH 6.0, to reproduce the pH-induced refolding/unfolding kinetics of h-apoMb. The need for five states was also confirmed in terms of the rate equation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Gibbs free energy difference between two states was determined by the ratio of the partition functions, which corresponded to the difference in the potential energies (represented as the exponents of the partition functions), which required a set of constrained parameters in a reference state (U in this study). Reference elementary rate constants ( k 0 kl ), which were equivalent to the reference activation free energies (eq ), and the fluorescence intensity of each species at pH 6.0 were obtained from a previous report on urea-induced refolding/unfolding of h-apoMb at 0 M urea and pH 6.0 . The reference elementary rate constants at pH 6.0 were constrained as fixed parameters to define the reference free energy of each state.…”
Section: Resultsmentioning
confidence: 99%